FIGURE 2. Pterois volitans larvae. A. 2.5 in The lionfishes: Comparative development of Pterois volitans, Dendrochirus barberi, and D. hemprichi (Scorpaeniformes: Scorpaenidae: Pteroinae) and discrimination of their early life stages from non-pteroine scorpaenid genera in the Western North Atlantic ... - Ditty, James G.; Malca, Estrella; Vásquez-Yeomans, Lourdes (Zenodo, 2024)
FIGURE 2. Pterois volitans larvae. A. 2.5 mm; B. 4.6 mm (pectoral-fin pigment omitted due to broken rays in larva illustrated); C. 6.0 mm; D. 8.5 mm; E. 9.3 mm; F. 9.8 mm; G. radiograph of aberrant 12.9 mm larva lacking first three dorsal spines and associated structures; arrow indicates position of anteriormost pterygiophore and underdeveloped fourth dorsal spine. All lengths in mm standard length (SL) post-preservation. Pigmentation enhanced in some images for illustration and detail purposes. ... : Published as part of Ditty, James G., Malca, Estrella & Vásquez-Yeomans, Lourdes, 2024, The lionfishes: Comparative development of Pterois volitans, Dendrochirus barberi, and D. hemprichi (Scorpaeniformes: Scorpaenidae: Pteroinae) and discrimination of their early life stages from non-pteroine scorpaenid genera in the Western North Atlantic, pp. 1-41 in Zootaxa 5446 (1) on page 11, DOI: 10.11646/zootaxa.5446.1.1, http://zenodo.org/record/11084543 ...